O ensino de geometria por meio de construções geométricas - Pimentel, Jailson (2013)
The purpose of this work is to develop an alternative methodology for teaching Geometry beginning in ninth grade level, with the purpose of awakening in student motivation through mechanisms that enhance deductive logical thinking. In this sense, geometry teaching based on geometric constructions with ruler and compass will be considered relevant, as textbooks generally abandoned this geometry teaching method in ninth grade. We will also focus some elaborations using the resources of practical software Geogebra. This work will be made and developed in two stages. The first one will consist of a questionnaire, which will include a review of the contents considered prerequisites for the second part. The second and main stage of this work is formed by geometric constructions with ruler and compass, and then elaborations using the practical features of the software Geogebra. For this, we will use a simple language, detailing step by step the construction of each geometric picture. However, we will limit ourselves to plane figures. The continuity proposal of the subject reaches the constructions through flat pattern of a picture in three dimensions. In general, the discipline “Geometric Drawing” is not present in the public schools curriculum. Thus, students, particularly the ones from elementary school, believe that the measure serves only to draw circles, and it can also be used as a measuring instrument. It is hoped that this work will not only contribute to an understanding of theoretical as well as the improvement of teaching practices in geometry classes, since the contents and methodologies used here are intended, primarily, to help mathematics teachers of basic education.